AB1125 PERFORMANCE OF ULTRASOUNDS TO ASSESS EROSION PROGRESSION IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Peran, M.; Allado, E.; Albuisson, E.; Couderc, M.; Ornetti, P.; Roux, C.; Grosse, J.; Chary Valckenaere, I.; Loeuille, D.
Abstract : Background: Ultrasonography (US) can detect more erosions than radiography (RX) at the joint level in rheumatoid arthritis (RA), especially at an early stage of the disease. Objectives: The aim of the study is to determine the ability of ultrasonography to detect erosion progression by the US Score for erosions (USSe), in early (less than 2 years disease duration (DD)) and late stage (more than 2 years DD) RA over two years of follow-up. Methods: Patients fulfilling ACR 1987 and/or ACR/EULAR 2010 criteria for RA were prospectively included. Clinical and demographic informations were recorded at baseline and hands and feet RX were scored according to the Sharp erosion score (SHSe). Erosive RA on RX was defined by the presence of at least three eroded joints (1). US examinations were performed at baseline and during the two years of follow-up. Erosions were scored by US on six bilateral joints (MCP 2, 3, 5 and MTP 2, 3, 5) with a four grade-scale to calculate total USSe. Erosive RA on US was defined by presence of one erosion ≥ 2mm (2). Inter-examiner reproducibility was performed on 14 patients in order to calculate the smallest detectable change (SDC), which was 2.3. Ultrasonographic progression was defined as a change in USSe > 2 (erosion change > SDC). Results: A total of 71 patients were included, 22 patients (31.0%) had early RA and 49 (69.0%) patients had late RA diseases. On RX, 30 (42.3%) patients were erosive at baseline with a mean SHSe at 29.4 (SD at 24.7). On US, 63 patients (88.7%) were classified as eroded. On US, erosions prevailed at baseline in MTP5 joints, then MCP2 and MCP5 joints on their lateral facets. During follow-up, 28 patients (39.4%) were classified as US progressors, 30 (42.3%) were stable and 13 (18.3%) considered as regressors (figure 1 ). In early RA disease, three of the four non eroded patients became eroded. USSe progressed in 11 patients (50%) while regression was observed in only one patient. In late RA disease, 17 patients (34.7%) progressed and 12 patients (24.5%) decreased significantly their USSe. Erosion progression prevailed on MTP 5 joints followed by MCP2 and finally MCP5 joints (figure 2 ). Conclusion: US structural examination is a highly reproducible method to assess erosion in RA disease. The USSe is able to detect structural changes (progression, stabilization and regression) in RA patients during a follow-up of two years especially in RA patients with short disease duration. References: [1]Van der Heijde D, van der Helm-van Mil AHM, Aletaha D, Bingham CO, Burmester GR, Dougados M, et al. EULAR definition of erosive disease in light of the 2010 ACR/EULAR rheumatoid arthritis classification criteria. Ann Rheum Dis. avr 2013;72(4):479‑81. [2]Roux C, Gandjbakhch F, Pierreisnard A, Couderc M, Lukas C, Masri R, et al. Optimization of ultrasonographic examination for the diagnosis of erosive Rheumatoid Arthritis in comparison to erosive hand Osteoarthritis. Eur J Radiol. sept 2019;118:10‑8. Disclosure of Interests: None declared